Analysis of Entomological Parameters Using RT-PCR Method The Post-Popm in Simbang Kulon Village, Buaran District, Pekalongan Regency - Hasan, Nurmaliza; Setyowati, Endang Ariyani; Rejeki, Dwi Sarwani Sri (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Lymphatic filariasis is spread almost throughout Indonesia, some areas are categorized as filariasis endemic areas. The endemicity of filariasis in an area is determined by the microfilariae number (MF rate) above 1% by means of a finger blood survey (SDJ). Simbang Kulon Village in Buaran District, Pekalongan Regency is one of the filariasis endemic areas with an MF rate of 2.65%. This study aims to measure the entomological parameters and molecular examination of the transmission of lymphatic filariasis in Simbang Kulon Village. This study used a survey with a cross-sectional study design. Mosquito catching was carried out using the Human Landing Collection and Resting method both inside and outside the house. The results of the mosquito catching were brought to the laboratory for rearing process for 14 days. Data were analyzed descriptively. The results of the identification of 50 mosquitoes found 94% Culex quinquefasciatus mosquitoes and 6% Culex vishnui mosquitoes. Parous rate, infection rate and infective rate of Culex quinquefasciatus and Culex vishnui were zero per cent. Culex quinquefasciatus had the highest relative abundance (23.5%). Based on the results of the analysis of research data, filaria larvae were not found in the mosquito body because the two Culex mosquito species had never laid eggs (nulliparous).